Relationship between transformational leadership, school culture and safety management in elementary schools in Pahang, Malaysia - Karuppiah, Chanthravalli (2018)
The current study is an attempt to explore the relationship between transformational leadership, school culture with safety management practices among headmaster in elementary schools in Pahang, Malaysia based on teacher perception. This study also investigates the level of transformational leadership, school culture and safety management practices. According to the literature review, number of studies on safety management practices in elementary are still very less and most of the study available is related to sports practice in school or in other fields. Besides that, more investigation is required on the dimension of transformational leadership and school culture in order to identify their contribution to safety management in school. Full-range leadership model (Bass and Avolio, 1995) associated with Multifactor Leadership Questionnaire (Bass and Avolio, 1997), Deming PDCA model (1993) associated with Questionnaire of Safety Values and Dimensions (QSVP) (Diaz Cabrera et.al, 2007) and School Culture Survey developed by Gruenert and Valentine (1998) were applied for data collection in this study. This study utilizes a stratified random sampling method by choosing 44 elementary schools and 374 teachers in 11 districts of Pahang state (Kuantan, Pekan, Raub, Kuala Lipis, Jerantut, Bera, Bentong, Temerloh, Cameron Highland, Maran and Rompin). Selected schools are including all types of school in urban and rural locations. Data analysis conducted by using descriptive statistics, Pearson Correlation Coefficient and multi regression methods. The results of descriptive analysis indicate that both transformational leadership and school culture dimensions were at high level where else safety management dimensions were at medium level among headmaster at elementary schools in Pahang. The result of this study showed that out of nine dimensions in safety management, only three dimensions were at high level. The rest of the dimensions were at medium level. The result of correlation analysis indicated that there is a positive, significant and high relationship between transformational leadership and overall safety management (r=.57, p=.00).The result of correlation analysis also indicated that there is positive, significant and high relationship found to be exist between school culture and overall safety management (r=.68, p=.00). This study proposed several recommendations to the Ministry of Education, headmaster, teachers and school administration to improve the level of safety management dimensions by practising transformational leadership dimension and school culture dimensions.